Psychosocial correlates of organized physical activity in Portuguese urban youth - Adilson Marques; Miguel Peralta; João Martins; Hugo Sarmento; Ash C. Routen; Francisco Carreiro da Costa
Abstract This study aimed to explore the association between psychosocial factors and organized physical activity (PA) in urban children and adolescents. Data on organized PA, psychosocial variables, and demographic characteristics were collected via questionnaires. Logistic regression analyses were used to examine the relationship between psychosocial correlates and organized PA. Analyses were run separately for different age groups. Results showed that children and adolescents with a greater positive attitude toward PA were more likely to be involved in organized PA. Ego orientation was associated with organized PA at the age of 13-15 years. Task orientation was related to PA participation at the age of 13-15 and 16-18 years. Perception of competence was related to participation at the age of 10-12 and 13-15 years. These findings suggest that interventions to increase the level of participation in organized PA in youth should focus on increasing students' perceived physical competence, attitude toward PA, and establishing a strong motivational task/mastery climate.